Determination and monitoring of tetracycline and degradation products in livestock slaughterhouse wastewater treatment plant effluent - Topal, Murat; Topal, E.ışıl Arslan; Öbek, Erdal (My University, 2023)
Aim of our study was the determination and monitoring of tetracycline (TC) and degradation products (DEP) in livestock slaughterhouse wastewater treatment plant (SWWTP) effluent. For this purpose, TC and DEP values in SWWTP were investigated. The concentrations of TC and DEP were monitored for 12 months. TC, 4-epitetracycline (ETC), 4-epianhydrotetracycline (EATC), anhydrotetracycline (ATC), and physicochemical parameters of pH, suspended solids (SS), BOD5, COD, and TP were calculated. The maximum TC concentration was determined as 1.68±0.08 µg/L in March and the minimum TC was 1.08±0.05 µg/L in January. The maximum ETC was 2.93±0.14 µg/L in March and April. The minimum ETC was 1.98±0.1 µg/L in January. EATC was 10.82±0.5 µg/L in September, and minimum EATC value was determined as 9.14±0.4 µg/L in March. The maximum ATC value was 8.62±0.4 µg/L in June and the lowest ATC value was 6.61±0.3 µg/L in September. Concentrations of TC and DEP detected in SWWTP effluent were listed in descending order as EATC> ATC> ETC> TC.
Keywords: Pollution; Drug; Slaughterhouse; Removal; Tetrcycline